Multiple Market Entry, Cost Signalling and Entry Deterrence - Srinivasan, Kannan (Management Science, 1991)
A low-cost incumbent may limit price to informatively signal her cost to an uncertain potential entrant, and therefore deter entry. We enrich this model by investigating the strategic pricing behavior of the incumbent when she operates in multiple markets. We demonstrate that the low-cost incumbent's ability to separate from a ghost high-cost type is enhanced when she combines her signalling effort across markets, instead of independent signalling in each market. We show that, in the combined least-cost signalling, the low-cost incumbent limit prices in each market. In an attempt to minimize dissipative but informative signalling costs, the low-cost incumbent may enter unprofitable markets, but exit after credible separation.